PERANCANGAN HOTEL RESORT KAWASAN WISATA ALAM BUKIT KELAM DI KABUPATEN SINTANG - Edi Iriwanto; Syaiful Muazir; Rudiyono Rudiyono (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Bukit Kelam is the largest monolith rock in the world beating Ayers Rock in Uluru, Australia. Bukit Kelam is located in Kelam Permai District, Sintang Regency, West Kalimantan. Bukit Kelam is can attract tourists with its uniqueness. This hill is also an iconic tourist attraction. This potential has not been accompanied by the accommodation in the fulfillment of the needs of visitors. Based on existing observations and data, lodging accommodation is not yet available in this area. Facilities are needed that can be a place of retreat for tourists in the form of a Resort hotel. There are also issues sourced from the official website of the Sintang Regency Investment Departement (DPMPTSP) regarding investment development in the form of hotel construction in Kelam Permai District. Resort Hotels are not only a lodge but can also be a medium for visitors to enjoy the natural potential in the Bukit Kelam area. The application of the design theme